Productivity and Economics of Improved Interventions in Existing Farming System Modules of Punjab - Rajni , Satpal Singh; S S Walia (Indian Journal of Extension Education, 2016)
Crop production along with dairy is the main farming system of Punjab. The improper tapping of the potentialities of each component in the system can make the system unviable. Crops+dairy+vegetables enterprise gave maximum net returns (` 1,50,831) which were followed by crops+dairy ( 1,26,580) and gave 56.2 per cent higher net returns over crops and 19.2 per cent over crops+dairy during first year. The crops+dairy enterprise showed 31.1 per cent more economic returns over the alone cultivation of crops. In the second year, the crop component of existing farming system provided gross returns of ` 1,13,235/ha with input cost of ` 49,560 and gave net returns of ` 63,675/ha. The livestock and vegetable component gave net returns of ` 1,05,495 and ` 18,762, respectively. Three different interventions were incorporated into the system so as to maximize net return per unit area per unit time. As rice crop requires more irrigation water, it was replaced with basmati and provided gross returns of ` 1,42,705/ha with net returns of ` 82,550/ha. Interventions in livestock and organic kitchen gardening component gave net returns of ` 2,32,865 and ` 27,505, respectively.